Study guides

☆☆

Q: 3m2 plus 6m2 divide by 3m?

Write your answer...

Submit

Still have questions?

Related questions

(3m+2n)(m+3n)

You can take 3m out of both of them, leaving 6m^2 + 3m + 4 over m

6m2 - 3mp =m (6m - 3p) =3m (2m - p)

(3m + 2)(2m - 5)

3m x 2m = 6 m2

The GCF of the coefficients and constants i 1. The GCF of the variables is also 1.

It's not very scientific, but I usually solve these things with a mixture of common sense and trial and error. Call it educated guessing. The 3 in 3m2 only has two factors, so your brackets will start out with 3m and m. (3m )(m ) All of the operational signs are pluses. The brackets will have them too. (3m + )(m + ) Now you're looking for factors of 64 that will solve the equation. 64 only has four factor pairs, so it won't take long to try them all. 64 and 1 won't work. 32 and 2 won't work. 16 and 4 won't work. (3m + 8)(m + 8) Check it using the FOIL method. (First, Outside, Inside, Last) 3m x m = 3m2 3m x 8 = 24m 8 x m = 8m (24m + 8m = 32m) 8 x 8 = 64 (3m + 8)(m + 8) = 3m2 + 32m + 64. It checks.

9m + 9m + 3m + 3m = 24m

3m + 7 = 5 Subtract 7 from both sides: 3m = -2 Divide both sides by 3: m = -2/3

If -3m+5=-22, then you do this math: -22-5= -3m. -22-5=-27, so if you take the negative signs away from -27 and -3m, divide 27 by 3 to get 9, therefore m=9.

3m+2=17 First, subtract 2 to get m on one side. 3m+2-2=17-2 3m=15 Divide by 3 to get m by itself. 3m/3=15/3 m=5 m equals 5.

-3m + 8 - 7 = -3m + 1

People also asked